Seniors in international residential tourism: Looking for quality of life - Oliveira, C.; Brochado, A.; Correia, A. (Anatolia, 2018)
This research was conducted in golf resorts, questioning tourists living in Portugal. Principal component analysis highlighted determinants of quality of life (QOL) of senior residential tourists. An ordered probit model evaluated what matters most to seniors seeking to achieve their desired level of well-being. Aesthetics of locations, perceived value, medical assistance, socialization, and community involvement contribute to decisions to establish a second residence in Portugal – either to ensure a good QOL at retirement or permit longer periodic stays. Results show that quality of neighbourhoods explains their aesthetic value and suggest that local social relationships matter. Beauty, security, and safety are equally important. This is one of the first studies suggesting that aesthetics in neighbourhoods explain QOL of senior residential tourists.